Endogenous or exogenous innovative development in companies on regional level? Case study - lubuskie voivoidship = Endogeniczny czy egzogeniczny rozwój innowacji w przedsiębiorstwach na poziomie regionalnym? Studium przypadku - województwo lubuskie - Świadek, Arkadiusz; Wiśniewska, Joanna (Zielona Góra: Faculty of Economics and Management Press)
At the moment endogenous growth theory has become increasingly popular in the world of science, particularly in developed countries. This article aims to show, for lubuskie case, the needs and sense of applying this theory in the Polish regions. Due to the low level of economic development of many Polish regions, including Lubuskie, they are unable to growth in a comparable rate as regions in developed countries. This explains the economic divergence between polish regions and the highly developed regions of Europe and the World. Stimulating economic growth are insufficient in such cases, because of the weakness of the internal factors in regions. Therefore it is important to strengthen an external impulses to keepinternal development. It means that the endogenous growth theory is no reason to exist, in conditions of poor Polish regions. Without external inputs there can't be convergences processes. Therefore, the economic development of the of Polish regions should be based on the exogenous growth theory.
Keywords: endogeniczny rozwój innowacji; ezogeniczna teoria wzrostu gospodarczego; przedsiębiorstwa w województwie lubuskim; wzrost gospodarczy; konwergencja regionów; endogenous innovative development; exogenous growth theory; lubuskie voivodeship; convergences processes